Highly enantioselective Pd-catalyzed synthesis of P-stereogenic supramolecular phosphines, self-assembly, and implication - Koshti, Vijay S.; Mote, Nilesh R.; Gonnade, Rajesh G.; Chikkali, Samir H. (Organometallics, 2015)
Metal-catalyzed asymmetric addition of a secondary phosphine to an aryl halide is one of the most efficient and reliable approaches for the construction of enantiopure carbon phosphorus bonds. An isolated Pd(II) complex (5) catalyzes the carbon phosphorus coupling reaction between tolylphenylphosphine (la) and 3-iodophenylurea (2b), which proceeds with an unprecedented enantiomeric excess (ee) of 97%. The generality of the strategy has been demonstrated by preparing a small library of a new class of P-stereogenic phosphines with an in-built hydrogen bonding motif for the first time. The P-stereogenic phosphines self-assemble on a metal template via deliberately installed hydrogen-bonding motifs and mimic the bidentate ligand coordination. Interestingly, when it was employed in asymmetric hydrogenation, the supramolecular phosphine {1-(3-(phenyl(o-toly)phosphanyl)pheny)ureal} (6b) produced the corresponding hydrogenated product with the highest enantiomeric excess of 99% along with excellent conversion, demonstrating the potential of these enantioenriched P-chirogenic supramolecular phosphines in asymmetric catalysis.

H-Bonding assisted self-assembly of anionic and neutral ligand on metal: a comprehensive strategy to mimic ditopic ligands in olefin polymerization - Mote, Nilesh R.; Patel, Ketan; Shinde, Dinesh R.; Gaikwad, Shahaji R.; Koshti, Vijay S.; Gonnade, Rajesh G.; Chikkali, Samir H. (Inorganic Chemistry, 2017)
Self-assembly of two neutral ligands on a metal to mimic bidentate ligand coordination has been frequently encountered in the recent past, but self-assembly of an anionic ligand on a metal template alongside a neutral ligand remains an elusive target. Such a self-assembly is hampered by additional complexity, wherein a highly negatively charged anion can form intermolecular hydrogen bonding with the supramolecular motif, leaving no scope for self-assembly with neutral ligand. Presented here is the self-association of anionic ligand 3-ureidobenzoic acid (2a) and neutral ligand 1-(3-(diphenylphosphanyl)phenyl)urea (1a) on a metal template to yield metal complex [{COOC6H4-NH(CO)NH2}{Ph2PC6H4NH(CO)NH2}PdMeDMSO] (4a). The identity of 4a was established by NMR and mass spectroscopy. Along the same lines, 3-(3-phenylureido)benzoic acid (2b) and 1-(3-(diphenylphosphanyl)phenyl)-3-phenylurea (1b) self-assemble on a metal template to produce palladium complex [{COOC6H4NH(CO)NHPh}{Ph2PC6H4NH(CO)NHPh}PdMePy] (5c). The existence of 5c was confirmed by Job plot, 1-2D NMR spectroscopy, deuterium labeling, IR spectroscopy, UV-vis spectroscopy, model complex synthesis, and DFT calculations. These solution and gas phase investigations authenticated the presence of intramolecular hydrogen bonding between hydrogen's of 1b and carbonyl oxygen of 2b. The generality of the supramolecular approach has been validated by preparing six complexes from four monodentate ligands, and their synthetic utility was demonstrated in ethylene polymerization. Complex 4a was found to be the most active, leading to the production of highly branched polyethylene with a molecular weight of 55700 g/mol and melting temperature of 112 degrees C.

Hydrogen bonding assissted supramolecular metal catalysis - Mote, Nilesh R.; Chikkali, Samir H. (Chemistry - an Asian Journal, 2018)
The process of catalyst screening and discovery still largely relies on traditional ligand-design approaches, which suffer from complex synthetic requirements and offer limited structural diversity. On the contrary, supramolecular chemistry offers the potential to harness multiple weak secondary interactions to deliver self-assembled catalysts with diverse structures or to orient substrates to achieve enzyme-like activity and selectivity. Herein, the application of hydrogen-bonding (H-bonding) interactions as a construction element and directing group in "supramolecular transition-metal catalysis" is critically reviewed and the current state-of-the-art in the field is presented. H-bonding interactions empower structurally simple ligands to deliver complex self-assembled catalysts, which have been found to catalyze a gamut of organic transformations, including hydroformylation, hydrogenation, and allylation reactions. As we will discuss, on many occasions, these supramolecular catalysts outperform their analogous covalently linked catalytic systems. The potential of H-bonding interactions as directing groups has recently been recognized by the scientific community and this Focus Review presents the role of hydrogen-bonding interactions in directing substrates to obtain excellent selectivities and activities in a range of catalytic transformations

Hydrogen-bonding-assisted supramolecular metal catalysis - Mote, Nilesh R.; Chikkali, Samir H. (Chemistry-An Asian Journal, 2018)
The process of catalyst screening and discovery still largely relies on traditional ligand-design approaches, which suffer from complex synthetic requirements and offer limited structural diversity. On the contrary, supramolecular chemistry offers the potential to harness multiple weak secondary interactions to deliver self-assembled catalysts with diverse structures or to orient substrates to achieve enzyme-like activity and selectivity. Herein, the application of hydrogen-bonding (H-bonding) interactions as a construction element and directing group in "supramolecular transition-metal catalysis" is critically reviewed and the current state-of-the-art in the field is presented. H-bonding interactions empower structurally simple ligands to deliver complex self-assembled catalysts, which have been found to catalyze a gamut of organic transformations, including hydroformylation, hydrogenation, and allylation reactions. As we will discuss, on many occasions, these supramolecular catalysts outperform their analogous covalently linked catalytic systems. The potential of H-bonding interactions as directing groups has recently been recognized by the scientific community and this Focus Review presents the role of hydrogen-bonding interactions in directing substrates to obtain excellent selectivities and activities in a range of catalytic transformations.

Neutral imino-methyl benzenesulfonate-ligated Pd(II) complexes and implications in ethylene polymerization - Deshmukh, Satej S.; Gaikwad, Shahaji R.; Mote, Nilesh R.; Manod, M.; Gonnade, Rajesh G.; Chikkali, Samir H. (ACS Omega, 2019)
A reaction between sodium 2-formylbenzenesulfonate and aniline revealed the near-quantitative (91%) formation of sodium-2-((phenylimino)methyl)benzenesulfonate L1. The identity of L1 was unambiguously ascertained using spectroscopic and analytical methods. The scope of this methodology was widened and various electron-donating amines were treated with sodium 2-formylbenzenesulfonate, and a small library of 6 imine ligands L2-L6 was generated. When L2 was treated with [(COD)PdMeCI], instead of the anticipated [L2PdMe(DMSO)] complex, the formation of [(DMSO)(2)Pd2Cl2Me2] Pd Dim was observed. Nevertheless, the desired imino-methyl benzenesulfonate-ligated palladium complex [L2PdMe(Lu)] C1 was obtained by in situ abstraction of chloride and addition of bulky 2,6-lutidine as the donor group. The observation of characteristic Pd-Me protons at 0.06 ppm and the corresponding carbon at -8.1 ppm indicated the formation of C1. These 1D NMR observations were corroborated by 2D C-H correlation spectra and mass analysis, and the existence of C1 was unambiguously ascertained. Along the same lines, L4 and L5 were treated with a palladium precursor to produce [L4/SPdMe(Lu)]-type complexes C2-C3 in 55-84% yield, and their identity was established by using a combination of spectroscopic tools, analytical methods, and single-crystal X-ray diffraction. The synthetic utility of C1-C3 has been demonstrated by utilizing these complexes in the insertion polymerization of ethylene to polyethylene.

Palladium-catalyzed insertion of ethylene and 1,1-disubstituted difunctional olefins: an experimental and computational study - Gaikwad, Shahaji R.; Patel, Ketan; Deshmukh, Satej S.; Mote, Nilesh R.; Birajdar, Rajkumar S.; Pandole, Satish P.; Chugh, Jeetender; Chikkali, Samir H. (ChemPlusChem, 2020)
Insertion or coordination copolymerization of ethylene with di-substituted olefins is challenging and the choice of di-substituted mono-functional olefin versus di-substituted di-functional olefin (DDO) appears to be decisive. Here we show that DDO-inserted species are amenable to ethylene insertion and polymerization. DDOs such as 2-acetamidoacrylic acid (AAA), methyl 2-acetamidoacrylate (MAAA), and ethyl 2-cyanoacrylate (ECA) were treated with palladium complex [P perpendicular to OPdMe(L)] (P perpendicular to O=kappa(2)-P,O-Ar2PC6H4SO2O with Ar=2-MeOC6H4; L=C2H6OS) and the existence of respective insertion intermediates in moderate yield (up to 37 %) was established. These intermediates were exposed to ethylene and corresponding ethylene-inserted products were isolated and characterized. A careful comparison with three model compounds confirmed ethylene insertion and polymerization. Thus, the combined experimental and computational investigations show that DDO-inserted species can undergo ethylene insertion and polymerization.
Keywords: Homogeneous catalysis; insertion copolymerization; Olefins; Palladium; Polyethylene

Controlled di-lithiation enabled synthesis of phosphine-sulfonamide ligands and implications in ethylene oligomerization - Mote, Nilesh R.; Gaikwad, Shahaji R.; Khopade, V, Kishor; Gonnade, Rajesh G.; Chikkali, Samir H. (Dalton Transactions, 2021)
Catalyst design for ethylene oligomerization has attracted significant interest. Herein, we report the synthesis of phosphine-sulfonamide-derived palladium complexes and examine their performance in ethylene oligomerization. Arresting a dilithiation intermediate of N-(2-bromophenyl)-4-methylbenzenesulfonamide (1) at -84 degrees C selectively produced N-(2-(bis(2-methoxyphenyl)phosphanyl)phenyl)-4-methylbenzenesulfonamide (L1A). However, the same reaction at -41 degrees C delivered a different ligand; 2-(bis(2-methoxyphenyl)phosphanyl)-4-methyl-N-phenylbenzenesulfonamide (L2A). The generality of our strategy has been demonstrated by preparing N-(2-(diphenylphosphanyl)phenyl)-4-methylbenzenesulfonamide (L1B) and 2-(diphenylphosphanyl)-4-methyl-N-phenylbenzenesulfonamide (L2B). Subsequently, L1A and L1B were treated with a palladium precursor to yield 5-membered complexes C1 and C2, respectively. In contrast, L2A upon treatment with palladium produced a 6-membered metal complex C3. Thus, a small library of 7 palladium complexes (C1-C7) were synthesized by varying the donor moiety (pyridine, DMSO, and acetonitrile). The identity of palladium complexes was unambiguously ascertained using a combination of spectroscopic and analytical methods, including single-crystal X-ray diffraction. The performance of the complexes C1-C7 was investigated in ethylene oligomerization and almost all of them were found to be active. The resultant ethylene oligomers were characterized using H-1 and C-13 NMR, MALDI-ToF-MS, and GPC. Detailed screening of reaction parameters revealed 100 degrees C and 40 bars ethylene to be optimal conditions. Complex C5 outperformed other complexes and produced ethylene oligomers with a molecular weight of 1000-1900 g mol(-1).

Ni-catalyzed highly enantioselective synthesis of sulfur protected P-stereogenic supramolecular phosphine - Koshti(S), Vijay S.; Chandanshive, Amol C.; Mote, Nilesh R.; Chikkali, Samir H. (Journal of Chemical Sciences, 2021)
As phosphines readily invert, the synthesis of P-chiral phosphines is a challenging task and has been rarely investigated. We report the synthesis of a nickel complex [Ni-((S,S)Me-FerroLANE)(phenyl)(I)] (Ni-Cat.1) and its performance in a P-C coupling reaction to generate P-chiral phosphine. The Ni-Cat.1 was synthesized by mixing ligand (S,S) Me-FerroLANE with the metal precursor [(diphenylphosphanyl)nickel(phenyl)(I)] in good yield. Ni-Cat.1 was characterized using different spectroscopic and analytical techniques. Treatment of racemic methyl(phenyl)phosphine (1) with 1-(3-iodophenyl)urea (2) produced the corresponding P-chiral supramolecular phosphine (3). Optimization of reaction parameters produced sulfur protected phosphine N-(3-(methyl(phenyl)phosphorothioyl)phenyl)formamide (3') with excellent enantiomeric excess (99% ee) and moderate conversion (51%).
Keywords: Asymmetric synthesis; Nickel catalyst; P-C coupling; P-Stereogenic phosphine; supramolecular ligands